PENGARUH PROFITABILITAS, KEKUATAN MODAL, PERTUMBUHAN KREDIT TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BISNIS 27 - MONICA, GENOVEVA (Jurnal Akuntansi AKUNESA, 2016)
Share price published by Bisnis 27 new published in 2009. This study used the period 2009-2014, to determine the development stock prices. 2013 marked global economic slowdown, falling commodity prices and a reversal of capital flows, has put pressure on the Indonesian economy during the year either through trade or financial. This study aims to determine whether the profitability, capital strength and credit growth effect on blue chip stocks. Profitability shown by some indicators such as ROA and ROE, capital strength using indicators CAR, while credit growth using indicators NPL and LDR. Multiple linear regression was used as a tool to analyze the problem. Data were collected from all banks listed on the Stock Exchange in 2009-2014. The study found that there are variables have a significant impact on stock prices, but not all of the individual variables have the same role. Variables: NPL have a negative impact on stock prices, while CAR, ROE, ROA and LDR do not. Thus, the authors conclude that in addition NPL can influence people to buy and sell their shares.